Fenomen wykonawstwa otwartego - Wójcikowska, Anna (Res Facta Nova, 2025)
Extensive research on the archival collection of Zygmunt Krauze (b. 1938) documenting over twenty years of activity of the “Warsaw Music Workshop” (Warsztat Muzyczny), a pioneering instrumental group specializing in new music, led the author to put forward a thesis about a new, “open” type of performance. This article is an attempt to define the concept of open performance, which is essentially an artistic attitude at the junction of areas of performance and creativity, that goes far beyond the score. The idea of open performance refers to Umberto Eco's concept of open work (opera aperta), according to which every modern work of art should be considered to have a specific “potential of openness”. The activity of the “Warsaw Music Workshop” is treated here as a model example of this “potentially open” attitude. Deliberation on open performance raises questions about the boundaries of interpretation, as well as responsibility for the final musical piece and artistic freedom.